Breeding site fidelity, and breeding pair infidelity in the endangered Carnaby’s Cockatoo Calyptorhynchus latirostris - Saunders, D.; White, Nicole; Dawson, R.; Mawson, P. (Pensoft Publishers, 2018)
The ecology and behaviour of the endangered Carnaby’s Cockatoo Calyptorhynchus latirostris have been studied in detail at Coomallo Creek in the northern wheatbelt of Western Australia from 1969 until the present. Results of research on this breeding population conducted on individually marked birds from 1970 to 1990 were compared with results from analyses of DNA taken from nestlings in the study area from 2003, 2005, and each year from 2009 to 2013. Analyses of DNA confirmed earlier findings about the stability of adult breeding pairs, and that females used the same breeding hollow they used previously, provided the hollow was not occupied when they returned to breed. When moving to another hollow, they chose a hollow in the same vicinity of the previous hollow. Analyses in 22 cases where DNA was obtained from both nestlings of a breeding attempt revealed that in six (27.3%) cases, the second egg was fertilised by a male not paired with the female. These extra-pair copulations were not suspected during the earlier study based on observations of individually marked birds.